Magnetic CuFe2O4 Nanoparticles Immobilized on Modified Rice Husk-Derived Zeolite for Chlorogenic Acid Adsorption - Tainara Ramos Neves; Letícia Ferreira Lacerda Schildt; Maria Luiza Lopes Sierra e Silva; Vannyla Viktória Viana Vasconcelos; Corrado Di Conzo; Francesco Mura; Marco Rossi; Gaspare Varvaro; Maryam Abdolrahimi; Simone Quaranta; Sandra Aparecida Duarte Ferreira; Elaine Cristina Paris (Magnetochemistry)
Adsorption has emerged as a promising method for removing polyphenols in water remediation. This work explores chlorogenic acid (CGA) adsorption on zeolite-based magnetic nanocomposites synthesized from rice husk waste. In particular, enhanced adsorbing materials were attained using a hydrothermal zeolite precursor (Z18) synthesized from rice husk and possessing a remarkable specific surface area (217.69 m2 g−1). A composite material was prepared by immobilizing magnetic copper ferrite on Z18 (Z18:CuFe2O4) to recover the zeolite adsorbent. In addition, Z18 was modified (Z18 M) with a mixture of 3-aminopropyltriethoxysilane (APTES) and trimethylchlorosilane (TMCS) to improve the affinity towards organic compounds in the final nanocomposite system (Z18 M:CuFe2O4). While the unmodified composite demonstrated inconsequential CGA removal rates, Z18 M:CuFe2O4 could adsorb 89.35% of CGA within the first hour of operation. Z18 M:CuFe2O4 showed no toxicity for seed germination and achieved a mass recovery of 85% (due to a saturation magnetization of 4.1 emu g−1) when an external magnetic field was applied. These results suggest that adsorbing magnetic nanocomposites are amenable to CGA polyphenol removal from wastewater. Furthermore, the reuse, revalorization, and conversion into value-added materials of agro-industrial waste may allow the opportunity to implement sustainability and work towards a circular economy.